2011
DOI: 10.1590/s1413-80502011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Tarifas de importação e evasão fiscal no Brasil

Abstract: ResumoA evasão de impostos, sobretudo por meio de subfaturamento das importações, sempre foi motivo de preocupação da administração aduaneira. Além da redução de receita tributária, a sonegação impõe perdas de competitividade aos importadores que assumem todos os encargos tributários, e reduz o grau de proteção à produção doméstica. O objetivo deste trabalho é verificar empiricamente a relação entre os níveis de tarifa aduaneira e o subfaturamento das importações no Brasil, e se este resultado é influenciado p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…Mishra et al (2008) confirmed these tariff evasion results for India and found a higher tariff semi‐elasticity of missing imports for products where enforcement of customs law, proxied by the mode of entry, was laxer. More recently, many studies have confirmed the tariff evasion result for various African countries (Arndt and Van Dunem, 2006; Levin and Widell, 2007; Bouet and Roy, 2009), North America (Stoyanov, 2009), Brazil (Kume et al, 2010), and for a cross section of 74 countries (Jean and Mitaritonna, 2010).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Mishra et al (2008) confirmed these tariff evasion results for India and found a higher tariff semi‐elasticity of missing imports for products where enforcement of customs law, proxied by the mode of entry, was laxer. More recently, many studies have confirmed the tariff evasion result for various African countries (Arndt and Van Dunem, 2006; Levin and Widell, 2007; Bouet and Roy, 2009), North America (Stoyanov, 2009), Brazil (Kume et al, 2010), and for a cross section of 74 countries (Jean and Mitaritonna, 2010).…”
Section: Literature Reviewmentioning
confidence: 91%
“…Hence, tariffs became the principal trade policy instrument and started to accurately reflect the level of protection faced by the national industry in Brazil. The average ad valorem nominal tariff was 30.5%, but varied substantially across industries, reaching 78.7% in the apparel industry (Kume et al, 2003).…”
Section: The Trade Policy Shockmentioning
confidence: 98%
“…Until then, while import duties were very high, the main source of import protection was a wide variety of non-tariff barriers, such as lists of banned products, quantity controls and government procurement restrictions. The protection level effectively faced by a given industry was significantly higher than nominal tariffs alone suggested, leading to a nontransparent structure of protection (see Abreu, 2004, andKume et al, 2003).…”
Section: The Trade Policy Shockmentioning
confidence: 99%
“…When something overseas arrives, along with its property certificate documents, the owner or company should proceed to the customs clearance to free its entrance. After that, a government area (the federal revenue office, "Secretaria da Receita Federal do Ministerio da Fazenda") investigates the authenticity of the declared information (Kume et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the import clearance was effected through the import declaration (DI), registered in the integrated foreign trade system (Siscomex). This import clearance presented: invoice (by the exporting company), bill of lading and freight forwarding (from the transport company), and registered information about the product packed (its single price, quantity, weight, and total cost) (Kume et al, 2011). However, Siscomex data was not enough to supply the government impositions -and new system designs and structures were created to assist those already there.…”
Section: Introductionmentioning
confidence: 99%